2017
DOI: 10.1007/s00167-017-4797-y
|View full text |Cite
|
Sign up to set email alerts
|

The quadrant method measuring four points is as a reliable and accurate as the quadrant method in the evaluation after anatomical double-bundle ACL reconstruction

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
2
10
0
1
Order By: Relevance
“…Femoral tunnel positions after anatomical DB‐ACLR were reported using the quadrant method on 3D‐CT images; the mean AMB value of Lf/L percentages were ranged from 16.9 to 27.7% [1, 9, 27, 40, 43]. The current deep–shallow position is consistent with the previous data.…”
Section: Discussionsupporting
confidence: 83%
“…Femoral tunnel positions after anatomical DB‐ACLR were reported using the quadrant method on 3D‐CT images; the mean AMB value of Lf/L percentages were ranged from 16.9 to 27.7% [1, 9, 27, 40, 43]. The current deep–shallow position is consistent with the previous data.…”
Section: Discussionsupporting
confidence: 83%
“…Compared with a simple radiograph, 3D-CT is conceptually similar to cadaver measurement techniques, with a perfect perspective of bony aperture and osseous landmarks [8]. Several studies have shown its excellent inter-and intra-rater reliability in the evaluation of femoral tunnel position [24,26], which was also proven in our research. The quadrant method has been extensively used in the evaluation of femoral tunnel position, but there are some non-negligible factors afecting its accuracy on 3D-CT. Iriuchishima reported that morphologic variations of Blumensaat's line may not only disturb the arthroscopic creation of tunnel placement but also inluence the postoperative results measured with the quadrant method.…”
Section: Discussionsupporting
confidence: 64%
“…After ACL reconstruction, the femoral and tibial tunnel locations were evaluated on a 3D‐CT according to the modified quadrant method [25]. The total sagittal length of the lateral condyle and the maximum depth of the intercondylar notch were measured and the femoral tunnel location was determined in terms of the percentage ratios in deep–shallow and high–low direction.…”
Section: Methodsmentioning
confidence: 99%